Konsep Perang dan Damai dalam Hukum Tata Negara Islam Perspektif Hukum Internasional dan HAM - Nadirah Aprilia Kayyirah Aprilila; Rihan Dwi Putri; Adelia Nur Insani; Kurniati Kurniati (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Islam, as a religion with a mission to provide mercy to all of nature, places welfare, justice and human protection as the main goals of sharia. Therefore, the concepts of war and peace should not be viewed only as tools of violence, but as part of siyāsah fiqh which is tied to maqāṣid al‑sharī‘ah. In Islamic constitutional law, jihad and war policies are within the authority of state leaders who are responsible for the stability and welfare of the people. However, in the context of modern Islamic countries, tensions arise between the claim of the primacy of sharia and the state's obligations to international law, especially international humanitarian law and human rights (HAM). This research discusses the issue of the law of war and peace in the context of Islamic constitutional law with the perspective of international law and human rights, and offers a reconstruction of the concept of the law of war and peace which emphasizes the principles of protection of civilians, justice, non-discrimination and compliance with war crimes within the framework of the ICC and the Rome Statute. From this analysis, it is concluded that the reconstruction of the concept of the law of war and peace in Islamic constitutional law does not conflict with Islamic teachings, but rather strengthens the integrity of sharia as a source of mercy and justice which is in line with human rights standards and international humanitarian law.